T/B‐cell interactions are more transient in response to weak stimuli in SLE‐prone mice. Issue 12 (12th November 2014) - Sinai, Parisa; Dozmorov, Igor M.; Song, Ran; Schwartzberg, Pamela L.; Wakeland, Edward K.; Wülfing, Christoph
Abstract : Changes in immune function during the course of systemic lupus erythematosus (SLE) are well characterized. Class‐switched antinuclear antibodies are the hallmark of SLE, and T/B‐cell interactions are thus critical. However, changes in immune function contributing to disease susceptibility are unknown. Here, we have analyzed primary T and B cells from a mouse model of SLE prior to the onset of disease. To allow cognate T‐cell activation with low affinity, we have developed a lower potency peptide ligand for the OTII TCR. T‐ and B‐cell couples formed less frequently and retained their polarity less efficiently preferentially in response to low‐affinity stimulation in SLE‐prone mice. This matched decreased recruitment of actin and Vav1 and an enhanced PKCΘ recruitment to the cellular interface in T cells. The induction of the GC B‐cell marker GL7 was increased in T/B cell couples from SLE‐prone mice when the T‐cell numbers were limited. However, the overall gene expression changes were marginal. Taken together, the enhanced cell‐couple transience may allow a more efficient sampling of a large number of T/B cell couples, preferentially in response to limiting stimuli, therefore enhancing the immune reactivity in the development of SLE.